Analysis of Semen Patterns in Male Partner of Infertile Couples: Semen analysis and male infertility - Tufail, Nazia; Bano, Nosheen; Ali, Saima; Wahab Salman, Nosheen; Mustafa Jadoon, Shandana; Ghafoor, Nosheen (Pakistan Journal of Health Sciences, 2022)
The 40-50% infertility cases are reported to be because of the male partner. For the accurate investigation of the cause of infertility in couples, the semen analysis is considered as the effective and fundamental tool. It not only assesses the sperm maturity and formation, but also provide with the insights into the quality and production of sperm. Objectives: To analyze the semen pattern of the infertile male. Methods: It was a retrospective study conducted at the Gynecology and Obstetrician department of Khawaja Muhammad Safdar Medical College, Allama Iqbal Memorial Teaching Hospital Sialkot. The study was carried out by collecting data from male infertile patients that visited tertiary care unit for a duration of six months from July 2021 to December 2021. All participants were fully aware of the objective of the study; as written consent was taken from them. The abnormal features of semen were analyzed. The various features of oligozoospermia and normospermia were studied and it was found. Results: A total of 260 individuals participated in this study, among them there were 204 that had primary infertility issues and 56 had secondary infertility issues. There were just 2 infertile male partners that were greater than 50 years of age. It was found that there were 56% partners that had normozoospermia and 39% infertile partners having asthenozoospermia, then it was followed by azoospermia condition which was seen in 28% patients. Conclusions: It was found that the asthenospermia, oligoasthenozoospermia and azoospermia are some of the contributors of male infertility.